Smoking in Health Science Students with Asthma - Georgios Krommydas; Evangelia Kotrotsiou; Vasilios Raftopoulos; Theodosios Paralikas; Konstantinos I Gourgoulianis; Paschalis-Adam Molyvdas (Canadian Respiratory Journal)
It is expected that asthmatic students in a health science department would avoid the hazards of cigarette smoking due to the knowledge they gain through their studies. Surprisingly, health science students with asthma had a higher prevalence of smoking than their healthy colleagues.